Axillary lymph node metastasis in gastrointestinal stromal tumor of jejunum: A case report (Indian Journal of Case Reports, 2020)
A gastrointestinal stromal tumor (GIST) is the most common mesenchymal tumor of the gastrointestinal tract accounting for <1% of all gastrointestinal tumors. The stomach is the most common primary site and the tumor spreads more frequently to the liver and peritoneum rather than lymph nodes. Herein, we present a rare case of a 78-year-old man who presented with GIST of the jejunum, which was surgically excised but developed isolated matted axillary lymph nodes 1 year after surgery. The axillary lymph nodes were excised, and histopathology confirmed metastasis from GIST of the jejunum. The patient was started on imatinib therapy and is completely disease free after 8 months of the second surgery